SISTEM INFORMASI AKUNTANSI DALAM PENGELUARAN DAN PENERIMAAN KAS PADA DANA BANTUAN OPERASIONAL SEKOLAH (BOS) DI SMK ISLAM NURUL IKHWAN SELABINTANA SUKABUMI - Muhammad Asep Tonny WR. (Nusantara Hasana Berdikari, 2021)
This study aims to understand the accounting information system in cash receipts and cash disbursements in school operational assistance funds (BOS). The variables used in this study are Accounting Information Systems, Cash Receipts and Cash Expenditures. The method used in this study is a qualitative method by utilizing data collection techniques and then conducting observations, interviews, documentation, triangulation and literature study. The data used in this study is primary data using observations and interviews with the Islamic Vocational School Nurul Ikhwan Selabintana Sukabumi. Where the resource persons in this study were the principal, school committee and BOS treasurer at Nurul Ikhwan Islamic Vocational School Selabintana Sukabumi. Data analysis techniques used are analysis before in the field, analysis during and after in the field, data reduction, data display and drawing conclusions. Based on the results of this study, it shows that the Accounting Information System on the School Operational Assistance (BOS) fund in schools is in accordance with the assistance of an internal control system to be able to produce credible and reliable information and can record errors that have occurred so that they can be corrected therein. there are external controls, administrative controls, operational controls, document controls and security controls. For Cash Receipts on BOS funds used have been based on the technical manual for School Operational Assistance (BOS) funds. In Cash Expenditures on BOS funds, schools have used Regular BOS funds to finance the operational implementation of education in their schools. It can be concluded that the Accounting Information System for Cash Receipts and Expenditures on the School Operational Assistance (BOS) fund is appropriate but there are still shortcomings on the side of the financial statements that are not available.